Executive gender diversity influence , transfer pricing , and profit management for tax avoidance with profitability as a moderating variable in mining companies listed on the Indonesia stock exchange in 2018-2022 - PUTRI FIRDIAH KARIM; NIRWANA; SYARIFUDDIN RASYID (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to examine and analyze the effect of executive gender diversity, transfer pricing, and earnings management on tax avoidance with profitability as a moderating variable. The objects of this research are mining companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. Determination of the sample using purposive sampling method which can be defined as a sampling technique based on certain criteria. The total population in this study was 47 mining companies whose shares were listed on the Indonesia Stock Exchange from 2018 to 2022. After the selection was made using the purposive sampling method, a sample of 3 1 companies was obtained for 5 years so that the total observations of this study were 15 5 annual reports, which then becomes 97 annual reports which are analyzed after outliers are made due to extreme data. The data collection used is secondary data and the data analysis used is with the help of the Statistical Product and Service Solution (SPSS) program Ver.2 9. The research results show that; 1) gender executive diversity has a negative effect on tax avoidance; 2) transfer pricing has a significant positive effect on tax avoidance ; 3) earnings management has a significant positive effect on tax avoidance; 4) profitability is not able to moderate the influence of executive gender diversity against tax avoidance; 5) profitability is able to moderate the effect of transfer pricing against tax avoidance; 6) profitability is able to moderate the effect of earnings management on tax avoidance.